2008
DOI: 10.1142/s1793292008001222
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS AND MICROSTRUCTURE OF A NOVEL TiO2 AEROGEL–TiO2 NANOWIRE COMPOSITE

Abstract: TiO 2 aerogel-10 mol% TiO 2 nanowire composite was prepared by a sol-gel technique with the addition of TiO 2 nanowires to TiO 2 sol, followed by supercritical drying in CO 2 . TiO 2 nanowires (anatase with minor rutile phases) as dispersoid were prepared by a hydrothermal process followed by calcination in air at 600 • C. The TiO 2 nanowires were dispersed in a 2-propanol/H 2 O/HNO 3 solution, and the mixture was added drop by drop to a tetrabutyl orthotitanate [i.e. Ti (IV) n-butoxide] solution in 2-propanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…4) with a water contact angle higher than 150 and self-cleaning properties [113], sulfated zirconia aerogels [114] (Chap. 6), TiO 2 aerogels [115] (Chap. 7), aerogel composites [115], and more exotic chalcogenide aerogels [116] (Chap.…”
Section: Recent Aerogel Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) with a water contact angle higher than 150 and self-cleaning properties [113], sulfated zirconia aerogels [114] (Chap. 6), TiO 2 aerogels [115] (Chap. 7), aerogel composites [115], and more exotic chalcogenide aerogels [116] (Chap.…”
Section: Recent Aerogel Developmentsmentioning
confidence: 99%
“…6), TiO 2 aerogels [115] (Chap. 7), aerogel composites [115], and more exotic chalcogenide aerogels [116] (Chap. 17).…”
Section: Recent Aerogel Developmentsmentioning
confidence: 99%
“…19 Semiconductor materials with different shapes (spheres, cubes, tubes, wires, rods, sheets and akes), sizes and dimensions can be synthesized by varying the method of preparation and calcination temperature. 20 Suzuki et al 21 suggested that there are still many possibilities for improving the photocatalytic activity of semiconductors, especially by altering their morphology. Campelo et al 22 showed that there are some benets in using nanosized Pd-containing photocatalysts since the Pd nanostructures have enhanced lightharvesting ability.…”
Section: Introductionmentioning
confidence: 99%
“…It is cheap and has been studied for long, especially for application in solar cells [9,10] or for its photocatalytic properties [11,12]. Different morphologies have thus already been developed, nanoparticles, nanotubes or even aerogels [13][14][15][16][17][18][19][20][21][22][23] for instance. Morphology is a major feature of PEMFC catalyst supports, especially at the cathode side, since it governs diffusion limitations related to gas diffusion towards (oxygen) and from (water) catalytic sites inside the cathodic catalyst layer.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%